2006
DOI: 10.1515/bc.2006.049
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrative DNA damage in animals and patients with inflammatory diseases in relation to inflammation-related carcinogenesis

Abstract: Infection and chronic inflammation are proposed to contribute to carcinogenesis through inflammation-related mechanisms. Infection with hepatitis C virus, Helicobacter pylori and the liver fluke, Opisthorchis viverrini (OV), are important risk factors for hepatocellular carcinoma (HCC), gastric cancer and cholangiocarcinoma, respectively. Inflammatory bowel diseases (IBDs) and oral diseases, such as oral lichen planus (OLP) and leukoplakia, are associated with colon carcinogenesis and oral squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
276
2
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(301 citation statements)
references
References 61 publications
11
276
2
12
Order By: Relevance
“…One mechanism whereby inflammation may contribute to the development of cancer is through the production of reactive oxygen and nitrogen species that can cause oxidative damage to DNA, proteins, and lipids. A study of multiple inflammation linked cancers, including CAC, found increased levels of oxidative damage specifically at cancer sites (Kawanishi et al, 2006). Continuous cytokine exposure induces an iNOS dependent up-regulation of ROS production and DNA instability (Seidelin and Nielsen, 2005), that leads to cancer.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…One mechanism whereby inflammation may contribute to the development of cancer is through the production of reactive oxygen and nitrogen species that can cause oxidative damage to DNA, proteins, and lipids. A study of multiple inflammation linked cancers, including CAC, found increased levels of oxidative damage specifically at cancer sites (Kawanishi et al, 2006). Continuous cytokine exposure induces an iNOS dependent up-regulation of ROS production and DNA instability (Seidelin and Nielsen, 2005), that leads to cancer.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Moreover, the overactivation of the MEK/ERK pathway in liver tumor cells confers resistance to TGFb-induced cell death through impairing NOX4 up-regulation and subsequent production of reactive oxygen species (ROS), which is required for an efficient mitochondrial-dependent apoptosis (11,12). The role of ROS in tumor biology has been extensively studied (13,14). ROS are chemically reactive molecules that fulfill essential functions in living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…ROS are chemically reactive molecules that fulfill essential functions in living organisms. A moderate increase in ROS can promote cell proliferation and differentiation (15,16), whereas excessive amounts of ROS can cause oxidative damages to lipids, proteins and DNA and lead to cell death (13,14). Several chemotherapeutic drugs exert their cytotoxic effects through the generation of ROS (17).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the relationship of persistent inflammation and stimulus to carcinogenesis and/or tumor progression was suspected. Chronic inflammation has been recognized as an important factor in carcinogenesis, such as gastric adenocarcino ma in He l i c ob ac t e r py l ori -in du c ed ga s tr i ti s , hepatocellular carcinoma in hepatitis virus infections, squamous cell carcinoma in oral lichen planus in humans, and in animal models such as cholangiocarcinoma in liver fluke infection and colon cancer in inflammatory bowel diseases [1,3]. In these instances, NO and relative reactive nitrogen and oxygen species are capable of tumor initiation and/or progression by nitrative and oxidative damage e.g.…”
mentioning
confidence: 99%
“…Significant amount of NO is generated via iNOS, so iNOS is identified as a biomarker for local excess production of NO. Additionally, NG and NT are used as markers of nitrative DNA and protein damage by NO, respectively [3,6]. COX2 is induced by NO and causes neovascularization via prostaglandin upregulation and promotes tumor progression [5].…”
mentioning
confidence: 99%